Aislamiento y evaluación de la resistencia a los antimicrobianos en salmonella spp, a partir de hisopados rectales y tejidos de cuyes (cavia porcellus) en criaderos de los cantones Pujilí y Latacunga de la provincia de Cotopaxi. - Yaguapaz Cortez, Ana Gabriela (2023)
This research aimed to determine the presence of Salmonella spp. through bacterial insulation methods from rectal swabs and tissues of guinea pigs from farms of Pujilí and Latacunga cantons, Cotopaxi province, to evaluate the patterns of antimicrobial resistance. So, 50 samples were studied in three hatcheries identified, such as A, B, and C, performing a microbiological analysis of isolation through the conventional method to detect Salmonella spp. proposed in ISO 6579: 2002 as an international reference, making pre-enrichment of samples in lactose broth, followed by enrichment with tetrathionate broth, and selective isolation in Bs and SS agar for confirmation by traditional biochemical tests through TSI, LIA, SIM, Citrate, Urea, and MRVP, for sensitivity analysis in 14 antimicrobials through the Kirby-Bauer dissemination method. The salmonella was isolated in 30% (15/50) of the analyzed samples. It was gotten antibiotic resistance profiles, and the results evidenced that the isolated bacteria are resistant to more than one antibiotic, being 100% to penicillin, and phosphoserine, followed by 93.3% to erythromycin, 86.7% to amoxicillin and ampicillin, 80% to the tetracycline and 66.7% for ampicillin/sulbactam. It was evident sensitivity of 100% in gentamycin, norfloxacin, ciprofloxacin, sulfamethoxazole/trimethoprim, and florfenicol, 80% to the enrofloxacin, and 73.3% to amoxicillin/clavulanic acid. Therefore, Salmonella spp. presents resistance mechanisms in multiple antibiotics, so it is essential, especially in Latin American countries, studies on multiresponse in this bacterium since one of the worrying antibiotics in this study resulted in phosphomicine, which is used first line and treated as the last treatment resort when all alternatives have failed, mainly when multiresistant bacteria cause infections., being a health risk because it can be used indiscriminately within the productive sectors so that it is necessary to establish and monitor appropriate strategies of its control.